ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UN AUTOSERVICIO DE PRODUCTOS DE PRIMERA NECESIDAD EN LA PARROQUIA MALACATOS, CANTÓN LOJA.” - JIMBO VILLALTA, MARJORIE NATHALIE (2016)
This thesis has the general objective "FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A SELF-STAPLES IN PARISH MALACATOS, LOJA CANTON" which is based on the importance is to undertake and contribute to the economy of the country, thus satisfy the people offering staples, increasing market share by applying efficient strategies, thus obtain economic incentive. Based on the first objective it is regarding the market study served to conduct an investigation to local families to study and thus set the preferences and choices of the plaintiffs through the survey and mathematical calculations, resulting in a potential demand 100% corresponding to 1929 families, a real demand of 83.94%, effective demand for 1599 families and considerable unmet demand for 1041 families of products to offer, taking into account marketing strategies to maintain consumer loyalty as well as attract new customers. 6 The technical study allowed us to determine the installed capacity is 60% of the unmet demand and capacity utilization in Year 1 90% Year 2 and 3 95% and in year 4 and 5 to 100%, ie the ability of the company to cater to consumers, and adequate microlocalization Macro Trace self-service for more welcomed by the people. As to administrative or legal study the organization of the company is a natural person, to conduct this study helped to meet the requirements of the law for its establishment, with its respective structural organization and functions manual for better performance of their daily activities. In relation to the objective, four a study of the possible sources of financing, where the National Finance Corporation was chosen because it is an institution that supports the advancement of the country, so that finances us with 91,90% of the total investment was made thatIt is $ 108,818.52. In addition to performing the financial evaluation it became clear that the investment project is acceptable by the net present value it is positive the result of $ 242,598.83, cost benefit of $ 1.15 where the company gets 0.15 for 7 every dollar invested, an Internal rate of Return of 79%, recovering the investment in 1 year, 4 months and 8 days later to have sensitivity in increased costs and decreased revenues during the period of its useful life. The methodology used to develop this work he did on the basis of the proposal to continue as the scientific method allowing studies using standard inductive, deductive, mathematical and statistical method, also investigative techniques as the survey and observation. Thus, it based on the results of the different phases of project confirming the feasibility of implementing the self in Malacatos parish, and this investment will contribute to the social, economic and trade development in the parish.